Fungemia in a university hospital: an epidemiological approach - Couto,Fabíola Maria Marques do (2011)
INTRODUCTION: Fungemia corresponds to the isolation of fungi in the bloodstream and occurs mostly in immunosuppressed patients. The early diagnosis and treatment of these infections are relevant given the serious threat to the affected patients and possible spread to other organs, often becoming fatal. The growing number of fungemia associated with poor prognosis resulted in this research aiming to diagnose and assess the epidemiological aspects of hematogenous infections by fungi. METHODS: The study included 58 blood samples collected within a 1-year period, from patients at the Hospital das Clinicas, Federal University of Pernambuco, by venipuncture in vacuum tubes. Blood samples were processed for direct examination and culture and identification, conducted by observing the macroscopic and microscopic characteristics, as well as physiological characteristics when necessary. RESULTS: Eight (13.8%) episodes of fungemia were identified, accounting for the total sample, and these pathogens were Candida, Histoplasma, Trichosporon, Cryptococcus, and a dematiaceous fungus. C. albicans was the prevalent species, accounting for 37.5% of the cases. Most affected patients were adult males. There was no predominance for any activity, and the risk of acquired immunodeficiency syndrome was the underlying pathology most often cited. CONCLUSIONS: The isolation of fungi considered as emergent species, such as C. membranifaciens and dematiaceous species, highlights the importance of epidemiological monitoring of cases of fungemia in immunocompromised patients, as the therapy of choice depends on the knowledge of the aethiological agent.